Model Pembelajaran Berbasis Integrasi Ilmu Keislaman dan Sains di Madrasah Ibtidaiyah - Lubis, Masruroh; Purnomo, Bagus; Syahrifin, M. (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
Education that integrates Islamic studies and science is an important challenge in Madrasah Ibtidaiyah, especially in the face of technological and scientific developments. This study aims to examine the implementation of an integrated Islamic studies and science-based learning model at Madrasah Ibtidaiyah MIS Al-Washliyah Labuhan Batu Utara and students' responses to the implementation of this model. This study employs a qualitative approach using the phenomenological method. Data were collected through observation, interviews, and document analysis. The results indicate that this learning model successfully connects scientific concepts with Islamic values, helping students understand science as part of Allah's creation. Students' responses to the learning model were highly positive, with increased motivation and a more holistic understanding of the relationship between science and religion. The implications of this study highlight the importance of developing a curriculum that integrates science and religion more comprehensively in Madrasah Ibtidaiyah. This research contributes to the development of relevant learning models, enriches students' learning experiences, and enhances their understanding of both disciplines.